Pola Pemberian MP-ASI pada Balita Usia 6-24 Bulan - Yuliati Amperaningsih; Siska Aulia Sari; Agung Aji Perdana (Politeknik Kesehatan Tanjung Karang, 2018)
WHO in WHA reported that 60% of direct and indirect infant deaths were caused by malnutrition and 2/3 of these deaths were associated with poor feeding practices in infants and children. Based on PSG results in 2016, Lampung and Bandar Lampung acute and chronic community nutritional problems (short prevalence ≥20% and thin ≥5%). The purpose of this study is to know the pattern of giving of breast milk in infants aged 6-24 months in the work area of Puskesmas Kota Baru New Town Bandar Lampung in 2017. This research is a qualitative research with phenomenology approach. Information obtained by conducting in-depth interviews, FGD, and observation. Informants in this study consisted of 5 main informants, 2 informants triangulation. The results showed that the form of MP-ASI have given for the age of 6-8 months and 12-24 months was appropriate but for 9-11 months age was not yet appropriate. The amount given is still less than the need with the frequency of giving 2-3 times a day plus 2 times a distraction. Type of MP-ASI is a local MP-ASI and MP-ASI manufacturer. How to serve in the form of dilute and liquid who fed by the mother. Raw food ingredients are stored separately with cooked foods. Feeding meals and suggestions are from their own mothers. Advice for MP-ASI counselors to provide regular and recorded counseling so that the stages and success of counseling can be evaluated.